Yahoo Web Search

  1. Ads
    related to sec
  1. Sort by

  1. Triple Sec can be considered a generic and inexpensive version of Cointreau. ... the amount for Cointreau as compared Triple Sec, you should.

    10 Answers · Food & Drink · 24/02/2007

  2. I have lost respect for the SEC due to its extremly weak non-conference scheduling...if you factor beating the cupcakes of the SEC (Miss & Miss St.) thats 6...

    16 Answers · Sports · 31/08/2007

  3. sec^3(x)dx = ⌠sec(x)sec^2(x)dx u=secx du=sec(x)tan(x)dx dv= sec^2(x)dx v = tan(x) ⌠sec^3(x)dx = sec(x...x)- ⌠(sec^2(x)-1)sec(x)dx ⌠sec^3(x)dx = sec(x)tan(x)- ⌠(sec^2(x)sec(x)dx + ⌠sec(x)dx transpose ⌠(sec^2(x)sec(x)dx to...

    3 Answers · Science & Mathematics · 20/03/2011

  4. Since secθ = 1/cosθ, consider the sign of cosθ (since secθ and cosθ will have the...cosθ < 0 in Quadrants II and III, secθ < 0 in Quadrants II and III as...

    1 Answers · Science & Mathematics · 23/08/2011

  5. sec^2(x) dx multiply and divide with tan x ∫tan x sec^2(x) dx / tan x let tan x = u sec^2(x) dx = du now the integral becomes...

    5 Answers · Science & Mathematics · 03/01/2010

  6. I = ∫sec^n(x) dx = ∫sec^(n-2)(x) sec^2(x) dx = ∫sec^(n-2)(x) dtan(x) = sec^(n-2)(x) tan(x) - ∫tan(x) (n-2) sec^(n-2) tan(x) dx = sec^(n-2)(x) tan(x) - ∫(n-2) sec^(n-2) tan^2(x) dx = sec^(n-2...

    3 Answers · Science & Mathematics · 05/02/2011

  7. sec(x) tan^4(x) dx For the integrand tan^4(x) sec(x), use the trigonometric identity tan^2(x) = sec^2(x)-1... the reduction formula, ∫ sec^m(x) dx = (sin(x) sec^(m-1)(x))/(m-1) + (m-2)/(m-1) ∫ sec^(-2+m)(x) dx, where...

    2 Answers · Science & Mathematics · 26/10/2010

  8. 1.) sec^ 4 - sec^ 2 = tan^ 4 + tan^ 2 =sec^2x(sec^2x-1) =sec^2xtan^2x =(1+tan^2x)(tan^2x) =tan^2x+tan^4x answer// 2.) (tan(a...sin^2(a)cos^2(a) ......1..............1 =------------- - ------------- ....cos^2a......sin^2(a) =sec^2(a)-csc^2(a) answer//

    3 Answers · Science & Mathematics · 21/03/2009

  9. sec(x) * dx => sec(x) * (sec(x) + tan(x)) * dx / (sec(x) + tan(x)) => (sec(x)^2 * dx + sec(x) * tan(x) * dx) / (sec(x) + tan(x)) u = sec(x) + tan(x) du = sec(x) * tan(x) * dx + sec(x)^2 * dx du / u ...

    4 Answers · Science & Mathematics · 17/04/2013

  10. Hello, ∫ tan²θ secθ dθ = let's start replacing tan²θ with sec²θ - 1...dθ - ∫ secθ dθ summing up, we have: ∫ tan²θ secθ dθ = ∫ secθ sec²θ dθ - ∫ secθ dθ let's integrate ∫ secθ sec²θ d...

    1 Answers · Science & Mathematics · 10/05/2011

  1. Ads
    related to sec
  1. Try asking your question on Yahoo Answers